2018
DOI: 10.1101/326603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of invitro susceptibility based on MICs and SQLE mutations with clinical response to terbinafine in patients with tinea corporis/cruris

Abstract: 24Recalcitrant dermatophytoses are on the rise and recent publications have documented high 25 minimum inhibitory concentrations (MICs) to TRB and squalene epoxidase (SQLE) mutations. 26 Biosystems). The amino acid sequence of SQLEp of all the investigated T. interdigitale in the 131 present study was compared with reference sequence of T. interdigitale (GenBank accession 132 number EZF33561). 133Statistical analysis was done on SPSS software version 21. One way ANOVA was used to 134 compare the geometric mean… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…There are some indications of a lack of in vivo correlation of in vitro resistance in dermatophytosis [ 35 ]. On the other hand, it was demonstrated that the odds of achieving a cure with terbinafine MIC < 1 µg/mL strains were 2.5 times the odds of achieving a cure with strains exhibiting MIC ≥ 1 µg/mL, suggesting a good in vitro and in vivo correlation [ 36 ]. Further studies are recommended to understand this complex problem of the in vitro/in vivo discordance.…”
Section: Discussionmentioning
confidence: 99%
“…There are some indications of a lack of in vivo correlation of in vitro resistance in dermatophytosis [ 35 ]. On the other hand, it was demonstrated that the odds of achieving a cure with terbinafine MIC < 1 µg/mL strains were 2.5 times the odds of achieving a cure with strains exhibiting MIC ≥ 1 µg/mL, suggesting a good in vitro and in vivo correlation [ 36 ]. Further studies are recommended to understand this complex problem of the in vitro/in vivo discordance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated emerging predominance of Trichophyton mentagrophytes as the causative organism in such cases . We have noticed that in some of these studies the causative agent of the chronic, relapsing dermatophytosis outbreak in India has been described as Trichophyton interdigitale . In our opinion, it is very likely that these T interdigitale strains isolated in Delhi and Chennai in India are, in fact, strains more closely related to the neotype of T mentagrophytes and are not strains of T interdigitale .…”
Section: Introductionmentioning
confidence: 87%
“…[4][5][6] We have noticed that in some of these studies the causative agent of the chronic, relapsing dermatophytosis outbreak in India has been described as Trichophyton interdigitale. [7][8][9] In our opinion, it is very likely that these T interdigitale strains isolated in Delhi and Chennai in India are, in fact, strains more closely related to the neotype of T mentagrophytes and are not strains of T interdigitale. 10 We therefore wish to underscore the importance of a common nomenclature of species in accordance with the new taxonomy of dermatophytes.…”
mentioning
confidence: 99%
“…We would also like to highlight that keeping pets is a rarity in India. Only two of the 64 tinea corporis/cruris patients, reported by Khurana et al had pets at home, and these were also apparently uninfected. Thus, to propose that a zoophilic species is the cause of the Indian epidemic is implausible.…”
Section: Introductionmentioning
confidence: 92%
“…There is also a rampant spread within families including young children and infants presenting with widespread tinea corporis/cruris has been commonly noticed (Figure C). In the study by Khurana et al 54.6% patients had an infected family member. We would also like to highlight that keeping pets is a rarity in India.…”
Section: Introductionmentioning
confidence: 99%